Antimicrobial Resistance in Neisseria gonorrhoeae: Proceedings of the STAR Sexually Transmitted Infection—Clinical Trial Group Programmatic Meeting. Issue 3 (March 2019) - Cristillo, Anthony D.; Bristow, Claire C.; Torrone, Elizabeth; Dillon, Jo-Anne; Kirkcaldy, Robert D.; Dong, Huan; Grad, Yonatan H.; Nicholas, Robert A.; Rice, Peter A.; Lawrence, Kenneth; Oldach, David; Shafer, William Maurice; et al.
Abstract : Abstract: The goal of the Sexually Transmitted Infection Clinical Trial Group's Antimicrobial Resistance (AMR) in Neisseria gonorrhoeae ( NG ) meeting was to assemble experts from academia, government, nonprofit and industry to discuss the current state of research, gaps and challenges in research and technology and priorities and new directions to address the continued emergence of multidrug-resistant NG infections. Topics discussed at the meeting, which will be the focus of this article, include AMR NG global surveillance initiatives, the use of whole genome sequencing and bioinformatics to understand mutations associated with AMR, mechanisms of AMR, and novel antibiotics, vaccines and other methods to treat AMR NG . Key points highlighted during the meeting include: (i) US and International surveillance programs to understand AMR in NG ; (ii) the US National Strategy for combating antimicrobial-resistant bacteria; (iii) surveillance needs, challenges, and novel technologies; (iv) plasmid-mediated and chromosomally mediated mechanisms of AMR in NG ; (v) novel therapeutic (eg, sialic acid analogs, factor H [FH]/Fc fusion molecule, monoclonal antibodies, topoisomerase inhibitors, fluoroketolides, LpxC inhibitors) and preventative (eg, peptide mimic) strategies to combat infection. The way forward will require renewed political will, new funding initiatives, and collaborations across academic and commercial research and public health programs.